Determinants for simultaneous binding of copper and platinum to human chaperone Atox1: hitchhiking not hijacking. - Maria E Palm-Espling (Public Library of Science (PLoS), 2013)
Cisplatin (CisPt) is an anticancer agent that has been used for decades to treat a variety of cancers. CisPt treatment causes many side effects due to interactions with proteins that detoxify the drug before reaching the DNA. One key player in CisPt resistance is the cellular copper-transport system involving the uptake protein Ctr1, the cytoplasmic chaperone Atox1 and the secretory path ATP7A/B proteins. CisPt has been shown to bind to ATP7B, resulting in vesicle sequestering of the drug. In addition, we and others showed that the apo-form of Atox1 could interact with CisPt in vitro and in vivo. Since the function of Atox1 is to transport copper (Cu) ions, it is important to assess how CisPt binding depends on Cu-loading of Atox1. Surprisingly, we recently found that CisPt interacted with Cu-loaded Atox1 in vitro at a position near the Cu site such that unique spectroscopic features appeared. Here, we identify the binding site for CisPt in the Cu-loaded form of Atox1 using strategic variants and a combination of spectroscopic and chromatographic methods. We directly prove that both metals can bind simultaneously and that the unique spectroscopic signals originate from an Atox1 monomer species. Both Cys in the Cu-site (Cys12, Cys15) are needed to form the di-metal complex, but not Cys41. Removing Met10 in the conserved metal-binding motif makes the loop more floppy and, despite metal binding, there are no metal-metal electronic transitions. In silico geometry minimizations provide an energetically favorable model of a tentative ternary Cu-Pt-Atox1 complex. Finally, we demonstrate that Atox1 can deliver CisPt to the fourth metal binding domain 4 of ATP7B (WD4), indicative of a possible drug detoxification mechanism.